Dermoscopic clues in the diagnosis of amelanotic and hypomelanotic malignant melanoma Pistas dermatoscópicas no diagnóstico de melanoma maligno amelanótico e hipomelanótico - Raquel Bissacotti Steglich; Carolina Degeon Meotti; Mariana Silveira Ferreira; Louise Lovatto; André Vicente Esteves de Carvalho; Carlos Gustavo Carneiro de Castro (Sociedade Brasileira de Dermatologia, 2012)
The clinical identification of amelanotic malignant melanoma (AMM) and hypomelanotic malignant melanoma (HMM) becomes difficult due to the lack of pigmentation and to the diverse clinical presentations. Dermoscopy is very useful in these cases, increasing the level of suspicion of malignancy. We report 4 cases of amelanotic malignant melanoma and hypomelanotic malignant melanoma with characteristic dermoscopic findings. Dermoscopy under polarized light demonstrates vascular polymorphism, globules and milky-red areas, in addition to chrysalis and multiple blue-gray dots. A identificação clínica de melanoma maligno amelanótico e hipomelanótico torna-se difícil devido à falta de pigmentação e às diversas apresentações desse tipo de tumor. A dermatoscopia é muito útil nestes casos, aumentando o grau de suspeição de malignidade. Relatamos 4 casos de melanoma maligno amelanótico e melanoma maligno hipomelanótico com achados dermatoscópicos característicos. A dermatoscopia com luz polarizada demonstra polimorfismo vascular, glóbulos e áreas vermelholeitosas, assim como crisálides e múltiplos pontos azul-acinzentados.